2015
DOI: 10.1017/s0025315415001964
|View full text |Cite
|
Sign up to set email alerts
|

The Bostrychietum community of pneumatophores in Araçá Bay: an analysis of the diversity of macrofauna

Abstract: A mangrove forest can harbour several macroalgal assemblages growing on pneumatophores, roots, stems and other hard substrates. These algae belong to various genera, most typically Bostrychia, and form a community called the Bostrychietum. This study describes the fauna associated with the Bostrychietum and the effect of emersion time on the community. Seasonal samples were collected from pneumatophores on an island in Araçá Bay in 2012, in two areas, one on the border of the island and one inland. Each pneuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
6
0
10
Order By: Relevance
“…Mites (Acari), for example, use Bostrychietum as habitat and source of food and their spatial distribution on rocky shores is closely related to the host position (Pfingstl 2013). As previously observed for Bostrychietum covering mangrove pneumatophores in the same area (García et al 2016), the rocky shore Bostrychietum in our study showed the presence of more resistant organisms like bivalves, acaris, and typically terrestrial animals, such as insects. The occurrence of these organisms in the lower limit of Bostrychietum bed in the midlittoral zone may reflect a close algal-fauna association and, in turn, a side-effect of insects using the algae as a proxy of the height in the shore.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Mites (Acari), for example, use Bostrychietum as habitat and source of food and their spatial distribution on rocky shores is closely related to the host position (Pfingstl 2013). As previously observed for Bostrychietum covering mangrove pneumatophores in the same area (García et al 2016), the rocky shore Bostrychietum in our study showed the presence of more resistant organisms like bivalves, acaris, and typically terrestrial animals, such as insects. The occurrence of these organisms in the lower limit of Bostrychietum bed in the midlittoral zone may reflect a close algal-fauna association and, in turn, a side-effect of insects using the algae as a proxy of the height in the shore.…”
Section: Discussionsupporting
confidence: 84%
“…(Montagne 1842) and that normally occurs on the upper portions of the intertidal zone (García et al 2016); algal turf -dominated by the red filamentous algae Gracilaria sp. (Greville 1830) that mostly occurs in the intertidal fringe.…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Even though gastropod densities presented some variation throughout the four sampling sites, the dominance of B. varium in all sites of Flamengo Bay was remarkable. Although this species often occurs in association with macrophytes, such high dominance levels are unusual, both in studies with other macrophyte species (Leite et al ., 2009; Creed & Kinupp, 2011; Barros & Rocha-Barreira, 2013; Zamprogno et al ., 2013; Queiroz & Dias, 2014; Duarte et al ., 2015; García et al ., 2015) and in studies with Sargassum sp. beds elsewhere on the Brazilian coast (Almeida, 2007; Jacobucci et al ., 2006; Longo et al ., 2014).…”
Section: Discussionmentioning
confidence: 97%
“…These macroalgae, along with microalgae, represent a major source of primary productivity in mangrove ecosystems (Karsten et al 1994a), as they produce organic matter and participate in nutrient cycling (McClusky & Elliot 2004). Furthermore, they act as microhabitats for several organisms, mainly protists and invertebrates (García et al 2016;Borburema 2017;Vieira et al 2018) and can be indicators of environmental quality (Melville & Pulkownik 2006;Fontes et al 2007;Melville & Pulkownik 2007) and food resource for consumers (Campos et al 2015).…”
Section: Introductionmentioning
confidence: 99%